Civil legal protection for land sale and purchase agreements in Serang city, Banten - Safiulloh Safiulloh; Aris Setyanto Pramono (Journal of Law Science, 2026)
This study discusses civil legal protection for land sale and purchase agreements in Serang City, which still face various problems, such as ownership disputes, document forgery, default, and non-compliance with land administration procedures. The purpose of this study is to analyze the forms of civil legal protection in the implementation of land sale and purchase agreements and to identify factors that influence the effectiveness of legal protection for the parties. This study uses a normative legal research method with a statutory and conceptual approach. Data were obtained through a literature review of laws and regulations, books, journals, and legal documents related to land sale and purchase. The results of the study indicate that civil legal protection for land sale and purchase agreements in Serang City is basically regulated in the Civil Code, the Basic Agrarian Law, and other land regulations. Legal protection is provided through the validity of the agreement, certainty of land rights, mandatory land registration, and dispute resolution through litigation and non-litigation channels. However, its implementation still faces obstacles in the form of low public understanding of legal procedures, lack of accuracy in document examination, and weak supervision of land administration. Therefore, it is necessary to increase legal socialization, optimize land services, and strengthen the role of land deed officials to provide certainty and more effective legal protection for the community in land sale and purchase transactions